2019
DOI: 10.1108/jmtm-12-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Managing the digital consumer: insights from Brazil and Spain

Abstract: Purpose The purpose of this paper is to analyze the concepts attributed to the use of technology in the digital environment and its relations with consumer behavior in Brazil and Spain. Design/methodology/approach This paper discusses the concepts that cover the use of technology in the relations between technological changes in e-commerce and consumer buying behavior in a digital world, using the Technical Availability Index (Techqual), by Parasuraman (2000), applied to Brazilian and Spanish consumers. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Seetharaman et al (2019) and Walwyn et al (2019) deal with industry and digitalisation (IIOT and energy). Monteiro et al (2019) and Saunila et al (2019) expound the problems of customer engagement in digital environment. Tambo and Filtenborg (2019) works out how IT4IT framework (see footnote 3) is linked to MoT;and Botha (2019) discusses whether intelligent machines will be capable to innovate in the future.…”
Section: Methods and Summary Of The Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Seetharaman et al (2019) and Walwyn et al (2019) deal with industry and digitalisation (IIOT and energy). Monteiro et al (2019) and Saunila et al (2019) expound the problems of customer engagement in digital environment. Tambo and Filtenborg (2019) works out how IT4IT framework (see footnote 3) is linked to MoT;and Botha (2019) discusses whether intelligent machines will be capable to innovate in the future.…”
Section: Methods and Summary Of The Papersmentioning
confidence: 99%
“…The use of such technologies is essential for South Africa. Monteiro et al (2019) ask how to manage the digital consumer. They investigate the customer engagement behaviour (CEB) in digital environment and analyses cases from Brazil and Spain.…”
Section: Rq3 Which Factors Can Augment the Adoption Process?mentioning
confidence: 99%
“…Lam et al [14] found that social media initiatives enhanced operational efficiency and helped corporate innovativeness. Social media can have a massive impact on consumer behaviors, and buying decisions are influenced by optimism, innovation, discomfort, and anxiety about social media usage [47]. Table I summarizes major findings on the impact of social media usage on various organizational performance over the past decade.…”
Section: ) Srm and Crm Practicesmentioning
confidence: 99%
“…Increasingly, evolving supply network management and technology contribute to the formation of highly specialized networks worldwide [1]- [4]. With a widely available dynamic technology network, social media has become an essential concept in most business models [5]- [8]. According to the Nielsen Company's [9] survey, the U.S. consumers spent nearly a quarter of their Internet time on social networking sites.…”
Section: Introductionmentioning
confidence: 99%
“…The use of information technology in the marketing of creative economic products and services is able to provide good added value to improve the best service to consumers [6][4]. This will increase growth in the creative economy business [7] The use of digital marketing in small and medium enterprises can increase sales [8]and digital marketing can provide good data processing support [9]. So, there is no reason not to apply this digital marketing technology [10].…”
Section: Introductionmentioning
confidence: 99%